(untitled) (Indian Journal of Arid Horticulture, 2025)
Zizyphus mauritiana, commonly known as ber, belongs to the family Rhamnaceae. It is an important fruit crop cultivated across India, with major growing regions in Madhya Pradesh, Bihar, Uttar Pradesh, Punjab, Haryana, Rajasthan, Gujarat, Maharashtra, and Andhra Pradesh. Ber is a drought-hardy fruit tree that can withstand saline and brackish water, making it particularly well-suited for arid regions. Due to its xerophytic traits and drought tolerance, it is often referred to as the "king of fruits" in arid areas. Among the many pests that attack ber, with 33 families identified as pests (Nair, 1986), the fruit borer Mungia mularachis (Meyrick) is particularly destructive, causing up to 70% yield loss during severe infestations (Karuppaiah, 2013). The pest damage has been most prominently observed in southern and western India (Pareek and Nath, 1996; Sonawane and Dorge, 1973). A field survey conducted in Kamalaka indicated that the fruit borer is a major pest in ber crops (Balikai, 1999). The reddish larvae of the fruit borer burrow into the fruit, feeding on the pulp and leaving visible faecal frass inside, which significantly affects fruit quality. The adult moths are small and dark brown in color. Given the significant crop losses caused by this pest, this study aims to evaluate newer insecticides and botanicals that are effective in controlling the fruit borer and improving ber crop yields.